A Quantitative Study of Early Childhood Care and Education Services Under the Age of Three: Evidence From Sichuan Province, China - Peng, Feng; Zhan, Xiaoyi; Yang, Bin; Tian, Yihao (Frontiers in Public Health, 2022)
In China, early childhood care and education services for children under the age of three are neglected to some extent. Based on survey data from the Health Commission in Sichuan Province of China, this study analyzes the situation of early childhood care and education services in Sichuan through a qualitative method, using an analytical framework of matching the demand and supply. The findings reveal a mismatch between demand and supply of early childhood care and education services. This gap is likely to have a negative impact on children's self-development, family stability, and even national construction. Drawing on the findings, suggestions for improving the mismatch between demand and supply are provided at the state, community and institution levels.